Benefits of Record Management For Scientific Writing (Study of Metadata Reception of Zotero Reference Management Software in UIN Malang - Wicaksono, Moch Fikriansyah; Nurpratama, Muhammad Rifky (Record and Library Journal, 2017)
Record creation and management by individuals or organizations grows rapidly, particularly the change from print to electronics, and the smallest part of record (metadata). Therefore, there is a need to perform record management metadata, particularly for students who have the needs of recording references and citation. Reference management software (RMS) is a software to help reference management, one of them named zotero. The purpose of this article is to describe the benefits of record management for the writing of scientific papers for students, especially on biology study program in UIN Malik Ibrahim Malang. The type of research used is descriptive with quantitative approach. To increase the depth of respondents answers, we used additional data by conducting interviews. The selected population is 322 students, class of 2012 to 2014, using random sampling. The selection criteria were chosen because the introduction and use of reference management software, zotero have started since three years ago.Â  Respondents in this study as many as 80 people, which is obtained from the formula Yamane. The results showed that 70% agreed that using reference management software saved time and energy in managing digital file metadata, 71% agreed that if digital metadata can be quickly stored into RMS, 65% agreed on the ease of storing metadata into the reference management software, 70% agreed when it was easy to configure metadata to quote and bibliography, 56.6% agreed that the metadata stored in reference management software could be edited, 73.8% agreed that using metadata will make it easier to write quotes and bibliography.